Systematic nursing consultation in basic care: experience report (Research, Society and Development, 2021)
Objective: to report the experiences of the systematization of nursing care with hypertensive users, describe the care and educational activities during the nursing consultation. Method: this is an experience report on the use of SAE in the nursing consultation held at the basic health unit. Results: during the systematized nursing consultation, self-care was encouraged, active listening was implemented and the care and educational plan were the main nursing interventions. Most users started to adhere to medication and non-medication treatment, with a significant change in their lifestyle. Conclusion: SAE, despite being the path to quality and organized care, is a major challenge for nursing. This opportunity enabled the experience of the nurse's performance in primary health care.